ChemInform Abstract: New Clathrates of Rb7.50(1)Tl0.50(1)Ge46 and K7.62(1)Tl0.38(1)Ge45.34(3). Issue 43 (7th October 2016) - Zhang, Hui; Mu, Gang; Huang, Fuqiang; Xie, Xiaoming
Abstract: The title type‐I clathrates are synthesized by solid state reactions of the elements (Ta tubes, 650 °C, 14 d) and characterized by powder XRD, SEM, and DFT calculations.